A Penetrating Facial Wound With Burn Injury. Issue 7 (October 2018) - Duan, Ran; Shi, Jun; Tremp, Mathias; Oranges, Carlo M.; Gao, Bowen; Xie, Feng; Li, Qingfeng
Abstract : Abstract: A patient presented with a complex penetrating facial wound by high temperature steel. The hot steel penetrated right temple, ethmoid bone, and maxillary sinus, and then exited from his left cheek. He kept his right eye but lost his sight. For functional and esthetic considerations, treatments were provided in a staged procedure. First, the debridement was performed under the endoscope. The dead bone was removed, broken teeth were extracted, and necrotic tissue was cleaned. The exposed wounds were cleaned, and dressing was changed daily until the exudation was widely reduced. Then, a 50-mL expander was placed in the left cheek, and an 80-mL expander was put in the scalp just before the defect in the temple area. Five months later, expander inflation was accomplished. Expanders were taken out and expanded flaps were transposed to cover the defect. At the same time, an anterolateral thigh flap was harvested to repair the inner lining of the cheek and the gingiva. Thereafter, several operations were performed to revise the wound scar and the remaining deformity. Both defects in the temple and left cheek were restored with a satisfactory functional and aesthetic outcome. The temporal area was repaired with haired expanded scalp, whereas the face was repaired with an expanded facial flap with similar texture and color. The oral commissure regained balance and integrity. The defect of the gingiva was repaired. A severe penetrating wound in the cranium and face can be nicely repaired using tissue expander and microvascular reconstruction.